Successful Bridge to Transplant in a Pediatric Patient Using the SynCardia 50 cc Total Artificial Heart. Issue 2 (February 2020) - Beasley, Gary S.; Allen, Kiona; Pahl, Elfride; Jackson, Lindsay; Eltayeb, Osama; Monge, Michael; Backer, Carl; Thrush, Philip
Abstract : Pediatric heart transplant candidates have the highest wait-list mortality of all organ candidates. Mechanical circulatory support has improved survival for many patients awaiting transplant. Biventricular mechanical circulatory support remains a particular challenge for pediatric patients. We present the smallest patient (body surface area 0.9 m 2 ) to date to receive the 50 cc SynCardia Total Artificial Heart, supported for 278 days before successful heart transplant.